HUBUNGAN ANTARA PENGETAHUAN DAN TINGKAT KECEMASAN VAKSINASI COVID-19 PADA LANSIA DI RW 10 KELURAHAN CIKUTRA - Hutami, Putri Adya; Sinaga, Anni; Prasetyo, Yunus Adhy (Institut Kesehatan Immanuel, 2023)
The Covid-19 vaccine can have an effect on causing feelings of worry and anxiety in the community. Anxiety, depression and cognitive impairment are often found at an older age. Knowledge can be one of the trigger factors for anxiety. The attitude of rejection arising from the public towards the Covid-19 vaccine is due to feelings of anxiety experienced by the community due to lack of knowledge. This study aims to analyze the relationship between the level of knowledge and the level of anxiety about Covid-19 vaccination in the elderly in RW 10 Cikutra Village. This research is a quantitative research type using a correlational method, with a cross sectional approach. This research instrument uses questionnaires. To measure anxiety levels using the Hamilton Rating Scale for Anxiety (HARS) questionnaire. The sample size was 62 respondents. The results of the study found a relationship between the level of knowledge and the level of anxiety about Covid-19 vaccination in the elderly in RW 10 Cikutra Village. The suggestion from this study is that it is hoped that the elderly in RW 10 Cikutra Village will get education about the level of knowledge of Covid-19 vaccination and can reduce the factors that cause anxiety levels in the elderly.